FOUNDATIONS OF PHYSICS - ADAMS, STEVE (MERCURY LEARNING & INFORM, 2023)
This updated edition is designed as a self-teaching, calculus-based introduction to the concepts of physics. Numerous examples, applications, and figures provide readers with simple explanations. Standard topics include vectors, conservation of energy, Newton's Laws, momentum, motion, gravity, relativity, waves, fluid mechanics, circuits, nuclear physics, astrophysics, and more. FEATURES:Designed as a calculus-based, introduction to the key concepts of physicsPractical techniques, including the collection, presentation, analysis and evaluation of data, are discussed in the context of key experiments linked to the theoretical spine of the work.
Keywords: elektronické knihy; electronic books